Preparing Future Mathematics Teacher Educators to Develop Mathematics Teacher Educator and Researcher Stances (LEARNing Landscapes, 2021)
The purpose of this paper is to support mathematics teacher educators (MTEs) to prepare their graduate students in becoming MTEs by creating a learning environment to develop epistemological stances. I present the components of my graduate seminar taught in a Practice-based Teacher Education program. The seminar aims to support graduate students to develop their stances and to address the “practice-theory” tension that exists between university courses and the work of teaching. I provide an overview of the class activities and present assignments that support graduate students in becoming MTEs.
Keywords: Mathematics Teacher Educator; epistemological stances; teaching practices